Multiplexed Protein Quantification in Maize Leaves by Liquid Chromatography Coupled with Tandem Mass Spectrometry: An Alternative Tool to Immunoassays for Target Protein Analysis in Genetically Engineered Crops - Hu, X. Tiger; Owens, Michaela A (Journal of agricultural and food chemistry, 2011)
A multiplexing liquid chromatography coupled with tandem mass spectrometry (LC−MS/MS) method to quantify three proteins in maize leaves was developed and validated. For each protein, a hybrid Q-TRAP mass spectrometer was operated in the information-dependent acquisition (IDA) mode to select optimal potential signature peptides. The respective signature peptides were then further optimized and quantified as protein surrogates by multiple reaction monitoring (MRM). Leaf crude extracts were subject to microwave-assisted trypsin digestion for 30 min and then injected directly onto a high-performance liquid chromatography (HPLC) column without further separation or enrichment. The minimum sample process enabled us to achieve high recovery and good reproducibility, with a throughput of 200 samples per day. Using recombinant proteins as standards, a linear dynamic quantitative range of 2 orders of magnitude was obtained (correlation coefficient > 0.997) with good accuracy (deviation from nominal concentration < 15%) for all three proteins. Our study demonstrates that LC−MS/MS can be used as an alternative to immunoassays to quantify multiple low abundant proteins in genetically engineered crops.